The role of mitral annular plane systolic excursion in prediction of acute blood loss in healthy voluntary blood donors - Güllüpınar, Birdal; Sağlam, Caner; Koran, Serhat; Turhan, Ajda; Ünlüer, Erden Erol (Medical communications, 2022)
Aim: The aim of this study is to compare the diameter of the inferior vena cava with mitral annular plane systolic excursion measurement in order to determine the volume loss before and after blood donation in healthy volunteers. Material and methods: The study was a singlecenter, prospective, cross-sectional study which included 46 healthy blood donors donating in a tertiary care hospital's blood bank. The inclusion criteria for the study were: volunteers aged 18-65 years, over 50 kg in weight, who met blood donation criteria, with hemoglobin values of 13.5 g/dL for males and >12.5 g/dL for females. After obtaining written consent, the systolic, diastolic, and mean arterial blood pressure along with the pulse rate of the donors were measured in standing and lying positions by the attending physician. Next, inferior vena cava and mitral annular plane systolic excursion measurements were made both pre and post blood donation. Results: The decrease in both inferior vena cava diameter and mitral annular plane systolic excursion values measured pre and post blood donation was found to be statistically significant (p <0.05). There was no difference between the other variables pre and post blood donation. Conclusions: Our study revealed that decreased inferior vena cava and mitral annular plane systolic excursion values correlated in determining blood loss post blood donation. Mitral annular plane systolic excursion may be useful to predict blood loss in the early stages of hemorrhagic shock.
Keywords: Point-of-Care Ultrasound; Emergency; Hypovolemia; Inferior Vena Cava; Mitral Annular Plane Systolic Excursion